Burnout em médicos e enfermeiros: estudo quantitativo e multicêntrico em unidades de cuidados paliativos em Portugal - Pereira, Sandra Martins (2017)
Theoretical Framework: Systematic contact with death is considered a risk factor for burnout in health, particularly for doctors and nurses who develop their professional activity in palliative care. Objectives: To study the syndrome of burnout in these professionals in Portugal. Methodology: A multicenter quantitative survey study. Results: Out of 142 professionals, 88 returned the completed questionnaire; of these, only 3% were in burnout and 13% at high risk of developing this syndrome. Professing a religion (p=.005) and having post-graduate education/training in palliative care (p=.011) were significantly and inversely associated with burnout. Conflicts with other professionals (p=.012) were significantly associated with developing this syndrome. Conclusion: Although the percentage of professionals with high levels of burnout in palliative care is low, there are risk factors that can be optimized to promote a higher well-being state among professionals.